2013
DOI: 10.1038/ncomms3828
|View full text |Cite
|
Sign up to set email alerts
|

Gate sequence for continuous variable one-way quantum computation

Abstract: Measurement-based one-way quantum computation using cluster states as resources provides an efficient model to perform computation and information processing of quantum codes. Arbitrary Gaussian quantum computation can be implemented sufficiently by long single-mode and two-mode gate sequences. However, continuous variable gate sequences have not been realized so far due to an absence of cluster states larger than four submodes. Here we present the first continuous variable gate sequence consisting of a single… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
90
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 51 publications
0
90
0
Order By: Relevance
“…From application view point, the generated entangled state has potential in one-way continuous-variable (CV) quantum computation [41]. By forming a cluster of entangling gates, it is possible to implement CV quantum computation using our system.…”
Section: Exciton-mode-mechanical-mode Entanglementmentioning
confidence: 99%
See 1 more Smart Citation
“…From application view point, the generated entangled state has potential in one-way continuous-variable (CV) quantum computation [41]. By forming a cluster of entangling gates, it is possible to implement CV quantum computation using our system.…”
Section: Exciton-mode-mechanical-mode Entanglementmentioning
confidence: 99%
“…By forming a cluster of entangling gates, it is possible to implement CV quantum computation using our system. The excitonmechanical mode entanglement might have advantages over that obtained between optical modes [41] due to the robustness of the entanglement as well as the availability of semiconductor and micro-electromechanical (MEMS) technologies. The exciton-mechanical mode entanglement also means entanglement with mechanical oscillator or MEMS, a significant progress towards entanglement of macroscopic objects.…”
Section: Exciton-mode-mechanical-mode Entanglementmentioning
confidence: 99%
“…The cluster states that facilitate MBQC can be generated via linear optics [5][6][7][8]. Four-mode and six-mode cluster states have been already used to implement arbitrary single-mode Gaussian gates [9], a two-mode Gaussian gate [10], and a gate sequence of these two [11]. Reshaping a cluster state [12] is possible through quantum erasing [13] and wire-shortening [14], which correspond to erasing and preserving the interaction gains between the nodes of the cluster state, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Cluster states, a type of multipartite entangled states, are basic quantum resources for one-way quantum computation [1,2]. Based on a prepared large scale cluster state, one-way quantum computation can be implemented by measurement and feedforward of the measured results [3][4][5][6]. It has been demonstrated that a local quantum network can be built by distributing a multipartite entangled state among quantum nodes [7][8][9][10].…”
mentioning
confidence: 99%